Enhance packet transmission using improved channel assignment in wireless mess network. (27th June 2019) - Sathyasri, B.; Ganesh, E.N.; Senthilkumar, P.
Summary: An efficient technique called channel Assignment (CA) is used to exploit the multiple non‐overlapping channels that improves capacity and decreases intervention in the wireless mesh network. Although it can reduce total network interference, there may be certain design issues by which network performance can be unfair. For maximizing the usage of wireless LAN network spectrum in these environments, many studies have discovered how to use the complete spectrum while transferring the data via mesh network. The proposed paper elaborates about the Enhanced Traffic‐Aware Channel Assignment Protocol. This protocol helps the mesh nodes present in the large‐scale mesh networks to assign the channels.